Effect of an Adapted Program of Physical Education in Children with Hearing Disability on Motor Coordination - Ochoa-Martínez, Paulina Yesica; Hall-López, Javier Arturo; Carmona López, Abel Alberto; Morales Ramírez, Mara Michell; Alarcón Meza, Edgar Ismael; Sáenz-Lopez Buñuel, Pedro (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2019)
Aim: To evaluate the effect of an adapted physical education program on students with hearing impairment on the motor quotient.Method: The design of the study was quasi-experimental, with convenience sampling, involving thirty-eight children with an average age of 7.4 ± 0.9 years, diagnosed with weakness or hearing loss, from two schools of the city of Mexicali, Baja California. Mexico. The participants were randomly divided into an experimental group (n = 23) and a control group (n = 15). The motor quotient was evaluated using the KTK children's body coordination test (Kiphard Körperkoordinationstest für Kindergarten and Schiling, as per the German acronym), through the tests, balancing movements of backs, jumps on one foot, lateral jumps and transposition on a platform. The program was carried out for four months, five times a week, with a duration of 50 minutes per session. The communication with the students was through the Mexican sign language, and the tasks performed emphasized motor coordination.Results: When comparing the results between groups of the motor quotient variable, with the mixed analysis of variance (ANOVA) 2 x 2, a doubly significant interaction between the groups and the measurements was observed (p = 0.01); the percentages of change (Δ %) were 26% for the experimental group, and 6.5% for the control group (Δ%).Conclusion: It is established that the application of a physical education program adapted for four months improves the motor coordination in children with hearing disabilities.